Impact evaluation of the strengthen PSNP4 institutions and resilience (SPIR) development food security activity (DFSA): Baseline report - Alderman, Harold; Bachewe, Fantu Nisrane; Gilligan, Daniel O.; Hidrobo, Melissa; Ledlie, Natasha; Ramani, Gayathri V.; Taffesse, Alemayehu Seyoum (2019)
Since its inception in 2005, the Productive Safety Net Program (PSNP) has been a cornerstone of the Ethiopian government’s strategy for poverty alleviation, disaster risk management and rural development. The PSNP provides food or cash transfers targeted to poor households in the form of payments for seasonal labor on public works (PW) or as direct support (DS) to households whose primary income earners are elderly or disabled. With more than 8 million beneficiaries, the PSNP is one of the largest social protection programs in Sub-Saharan Africa. The PNSP has played an important role in improving the lives of poor Ethiopian households by reducing household food insecurity, increasing asset holdings and improving agricultural productivity (Berhane et al. 2014; Hoddinott et al. 2017). The fourth phase of the Productive Safety Net Program (PSNP4) began operating in 2016. Under PSNP4, the Government of Ethiopia (GOE) undertook a new round of targeting to identify client households. GOE also added a new objective to the PSNP to improve the nutritional status of women and children by better linking PSNP clients to health and nutrition services and through nutrition conditionalities (World Bank 2014). PNSP4 also included an enhanced livelihood transfer program to strengthen livelihoods and build assets, seeking to improve on the performance past livelihood transfer components of the PSNP.